Library 5.0: New roles for the library in curriculum - Guldberg, Helle; Præcius, Daniel; Gundtoft, Martin; Franck, Frederick Lehmann; Fallentin, Ida; Winding, Jonas; Clemmensen, Pia; Olsen, Stine Lian (Septentrio Conference Series, 2020)
The library as pioneer in the development of study competencies for individual student retention and support. At KEA (Copenhagen School of Design and Technology), we have implemented a newly developed study competencies concept throughout our study programmes. The concept is designed and developed by the library staff and aims to support the individual student during the full length of his/her course of study. Our focus is on student centered learning (SCL), retention, completion and matching the complex requirements of the work place of tomorrow. In order to actively support the transformation from pupil to student, we have developed and implemented the concept “Study competencies – study-supporting activities”. Thus, enabling our students to complete their studies, whilst contributing to academically stronger graduates. Specifically, we are providing our students with tools and techniques to manage large amounts of information, understand academic language, structure their time, increase reading speed, apply new knowledge/trends and master the art of problem solving. In short, all essential study techniques and knowledge competencies whilst studying, but also in order to strengthen the students’ transition to a future workplace environment. The subjects are divided into modules. Each module includes learning objectives, teaching descriptions, videos, assignments and quizzes. All modules and tools are digitally accessible anytime anywhere for both faculty and students. As part of the concept, we have also developed an app – 5 korte (5 short) with five short touchdowns on source criticism, note taking, study reading, time management and research. The concept is scalable, integrated in the curriculum and follows a progression that supports the student throughout the course of study. We have based our method on co-creation and iterative processes involving faculty and students throughout the entire development process.